2000
DOI: 10.1046/j.1526-4637.2000.99104.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Zygapophysial Joint Blocks: The Travesty of Cost-Effectiveness

Abstract: Objective. The aim of this study was to develop equations by which the costs could be compared of various models of performing diagnostic blocks for spinal pain.Design. Algorithms were elaborated describing different strategies for the diagnosis of cervical or lumbar zygapophysial joint pain using placebo-controlled diagnostic blocks, comparative local anaesthetic blocks, or no control blocks, and its treatment with radiofrequency neurotomy. For each step in each algorithm cost functions were applied. Summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 19 publications
1
46
0
1
Order By: Relevance
“…In a randomized, comparative cost-effectiveness study comparing zero, one and two blocks before lumbar facet RF denervation, whereas two blocks was associated with the highest RF denervation success rate, the highest overall success rate and lowest cost per effective procedure was noted in the zero-block group [92]. Reasons for this finding, which is supported by theoretical computations [93], include the absence of false-negative blocks and the high placebo response rates for procedures [94].…”
Section: Patient Selectionmentioning
confidence: 87%
“…In a randomized, comparative cost-effectiveness study comparing zero, one and two blocks before lumbar facet RF denervation, whereas two blocks was associated with the highest RF denervation success rate, the highest overall success rate and lowest cost per effective procedure was noted in the zero-block group [92]. Reasons for this finding, which is supported by theoretical computations [93], include the absence of false-negative blocks and the high placebo response rates for procedures [94].…”
Section: Patient Selectionmentioning
confidence: 87%
“…We identified two studies evaluating the cost-effectiveness of other types of spinal nerve injections [zygapophyseal (facet) joint injections and medial branch (facet nerve joint) blocks]. 47,48 Although these studies provide indirect evidence that diagnostic injections in the spine can influence the percentage of patients receiving surgery and the cost of care, they do not provide direct evidence on the costeffectiveness of diagnostic SNRB in patients with LR. We therefore constructed an economic model based on evidence from our SR on the diagnostic accuracy of SNRB and the wider literature on the costs and outcomes of diagnosis and treatment of radiculopathy.…”
Section: Review Of Existing Cost-effectiveness Evidencementioning
confidence: 99%
“…18 Theoretical cost analyses have confirmed these results. 19,20 The search for ways to improve the selection of patients for facet joint denervation is complicated by the fact that most studies have demonstrated either no or only a weak association between historical and physical examination findings and injection-confirmed facetogenic pain 21,22 and between clinical findings and denervation outcomes. 9-11 Similar weak associations have been found for radiological imaging and the results of facet interventions.…”
Section: Methods: a Multicenter Prospective Study Was Performed In 223mentioning
confidence: 99%